Improvement of Mathematics Learning Outcomes Build The Space Through Media Three Class 2 Student Dimensions SDN Palebon 02 Semarang - Nining Nur Syarifah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Mathematics learning media is very necessary to support student learning outcomes. Three-dimensional media can be used as an alternative solution for teaching space building materials. Three-dimensional media is a group of media without projection whose presentation is visually three-dimensional. This media group can take the form of an original object both living and dead, and can also be tangible as an imitation that represents the original (Santyasa, 2007: 15).The purpose of this study was to improve the quality of Mathematics learning material through the use of three dimensional media. This research is a classroom action research (PTK) which is conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 20 grade II students of SDN Palebon 02 Semarang, with a total of 20 students. The research instruments were observation sheets, learning test results and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The finding of this research is that the use of Three Dimensional Media can improve the quality of students' Mathematics learning on Building Space material in class II SDN Palebon 02 Semarang. The results showed that the percentage of student learning activities in cycle I 74.5% increased in cycle II to 91.5% and the percentage of the number of students who completed the learning outcomes in cycle I 61.8% increased in cycle II to 100%.